2019
DOI: 10.21577/0100-4042.20170399
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento De Metodologia De Revelação De Impressão Digital Latente Com Chalconas

Abstract: Recebido em 12/02/2019; aceito em 10/07/2019; publicado na web em 26/08/2019 DEVELOPMENT OF METHODOLOGY OF LATENT FINGERPRINT REVELATION WITH CHALCONES. Fingerprints are unique for each individual contributing to human identification in forensic cases. Visualization of latent fingerprints usually involves the use of a chemical substance that creates a contrast between fingerprint residues and the surface on which the print was deposited. Commercial powders used as fingerprint developers by papilloscopy have re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
4
0
4
Order By: Relevance
“…These studies concentrated on the chemical imaging of fingermarks and spectrometry as can be observed on Figure 6. Considering the articles published with at least one author with Brazilian affiliation, the focus of the studies at the same period was the synthesis and applications of new fingerprint developers materials [3][4][5][6][7][8][9][10] . These studies aimed to identify low-cost materials, some based on natural resources, which presented greater contrast in different situations, such as dark backgrounds and metallic surfaces, when compared to traditional developers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies concentrated on the chemical imaging of fingermarks and spectrometry as can be observed on Figure 6. Considering the articles published with at least one author with Brazilian affiliation, the focus of the studies at the same period was the synthesis and applications of new fingerprint developers materials [3][4][5][6][7][8][9][10] . These studies aimed to identify low-cost materials, some based on natural resources, which presented greater contrast in different situations, such as dark backgrounds and metallic surfaces, when compared to traditional developers.…”
Section: Resultsmentioning
confidence: 99%
“…Balsan et al 9 analyzed the application of different chalcone powder that it is a technique with potential application for porous materials.…”
Section: Fingermark Developmentsmentioning
confidence: 99%
“…Inúmeras pesquisas científicas estão sendo direcionadas para ao aprimoramento de fatores como toxicidade, sensibilidade, superfície, eficiência dos materiais e métodos de revelação, utilizando de técnicas espectroscópicas apropriadas e abordagens baseadas em nanopartículas dopadas com terra-raras (Bhatia, 2021;Bleay, et al, 2018;Hazarika & Russell, 2012; Research, Society and Development, v. 11, n. 11, e38111133371, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i11.33371 5 Naik et al, 2021;Wang et al, 2017), corantes naturais (Garg, et al, 2011;Pacheco et al, 2021), compostos orgânicos (Balsan et al, 2019;Gayathri et al, 2021) e quantum dots (QDs) (Becue et al, 2009;Moret, et al, 2013;Pandiyan et al, 2020).…”
Section: Corantes áCidosunclassified
“…Entretanto, se faz necessário o uso de técnicas específicas e o desenvolvimento de materiais que facilitem o trabalho dos peritos, como por exemplo no caso da revelação de impressão digital, em que podem ser utilizados pós, sprays, soluções e dispositivos para revelar manchas de sangues e outras secreções latentes (Bécue et al, 2009;Firmino et al, 2021;Li et al, 2016;Naik et al, 2021;Sobral et al, 2016;Wang et al, 2017). As impressões digitais são um dos tipos mais úteis e importantes de evidência física, uma vez que cada indivíduo apresenta um padrão único na pele do dedo (Balsan et al, 2019). Neste contexto, a revelação de impressões digitais latente com sangue ainda apresenta algumas inconsistências, sendo estas geralmente deixadas na cena do crime, todavia, pode carregar provas valiosas para a solução de um crime.…”
Section: Introductionunclassified
“…In this scenario, rice husk is an interesting waste material that can be used for the biosynthesis of gold nanoparticles [10] or for lignin extraction [11]. Moreover, organic molecules, such as curcumins [12] and chalcones [13], have also been efficiently applied in LFM development.…”
Section: Introductionmentioning
confidence: 99%